THE EFFECT OF PERSONALITY AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. BPP AIR BALAM - Mardahleni, Mardahleni; Eko Putra; Wildan, Wildan (Ikatan Dosen Menulis, 2024)
This study aims to determine the influence of personality and organizational commitment on employee performance at PT BPP Air Balam. This type of quantitative research aims to determine how personality and organizational commitment influence employee performance at PT BPP Air Balam. The population in this study consists of all factory employees. The sample in the study consisted of 54 respondents. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, regression tests, F tests, and T tests. The results of this study indicate a positive and significant influence of personality variables on employee performance variables at PT BPP Air Balam. This can be seen from the regression coefficient of 2.751 with a significant level of 0.008 (<0.05). The organizational commitment variable has a positive and significant effect on employee performance variables at PT BPP Air Balam; this can be seen from the regression coefficient value of 2.348 with a significant level of 0.023 [<0.05]. This study concludes that personality and organizational commitment influence employee performance at PT BPP Air Balam by 79.5%, while the remaining 20.5% is influenced by other factors.